1997
DOI: 10.1017/s0022226797006488
|View full text |Cite
|
Sign up to set email alerts
|

Forms of address and terms of reference

Abstract: This paper examines the relationship between the use of names and other words in address and in reference : how does the way that speaker A addresses B differ from the way that A refers to B, and what are the factors affecting this difference ? The study, based on observation and interviews, attempts both to solve a problem in pragmatics and to help historical linguists and others who need to know the extent to which it may be justified to extrapolate from referential to address usage and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 9 publications
6
54
0
4
Order By: Relevance
“…On the other hand, some children did not use kinship terms for their parents. These children did not acknowledge their parent-child relationships (Dickey, 1997). Because parent-child relationships have fundamental effects on children's mental health, the unacknowledged forms of address to their parents were relevant to their mental problems (Yokotani, in press;Yokotani & Hasegawa, 2011b).…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some children did not use kinship terms for their parents. These children did not acknowledge their parent-child relationships (Dickey, 1997). Because parent-child relationships have fundamental effects on children's mental health, the unacknowledged forms of address to their parents were relevant to their mental problems (Yokotani, in press;Yokotani & Hasegawa, 2011b).…”
Section: Future Researchmentioning
confidence: 99%
“…Yokotani (in press) sampled 329 Japanese college students and found that acknowledged kinship terms predicted participants' frequent communication and their satisfaction with father-child relationship. Dickey (1997) interviewed native speakers of English, German, Italian, Czech, Swiss, and Greek. He found that acknowledged kinship terms were used within acting parent-child relationships but not within stepparent-child relationships.…”
mentioning
confidence: 99%
“…Braun also covers a wide variety of variables e.g., family members, addressing God, children, animals, neighbors, places of employment, university, which branches out from Brown and Gilman's concentration on power and solidarity. Dickey (1997) works with experimental data and focuses on the factors which influence the way one can be referred to stating "[the ways] are virtually infinite" (259). Her aim is to explain "how does the way that speaker A addresses B differ from the way that A refers to B, and what are the factors affecting this difference?"…”
Section: Literature Reviewmentioning
confidence: 99%
“…Establishing and maintaining social relationships. Dickey (1997), same as Zwicky, compared vocative noun phrases and referential noun phrases. She focused on the status relationship between the interlocutors.…”
Section: Vocative Interjection and Honorificsmentioning
confidence: 99%